A new open absorption heat pump for latent heat recovery from moist gas. (April 2015) - Ye, Bicui; Liu, Jun; Xu, Xiangguo; Chen, Guangming; Zheng, Jiao
Highlights: A new open absorption heat pump system was proposed. The new system aims at recovering latent heat from low-temperature moist gas. The new system can utilize a lower temperature range of heat source. COPh and heat recovery efficiency is high with the production of high-temperature steam. Increasing generation temperature and humidity of gas is beneficial for the new system. Abstract: Conventional drying processes discharge high humidity gas to the atmosphere. The exhaust gas contains large amount of energy. The direct discharging would result in relatively large energy waste. In order to improve the thermal efficiency of drying process, in this paper, a new open absorption heat pump system was proposed, which aims at recovering the latent heat from exhausted moist gas and producing steam for reutilization. The working principle was discussed in detail and thermodynamic models were established to analyze the performance of the new system. The new system can work under both single-stage and double-stage modes. Simulation results showed that the new system could utilize a heat source with lower generation temperature compared with that utilized by a traditional open absorption system. The temperature range of heat source for the double-stage mode is 130–160 °C, and that for the single-stage mode is 160–175 °C. The new system also eliminates the limitation of traditional close absorption system, whose evaporation temperature has to be lower than the dew point temperature of discharged moist gas to recover the latent heat of water steam. Simulation results also indicated an improved COPh of the new system compared with that of double-stage close absorption heat pump system. The COPh of the new system varied from 1.52 to 1.97 and the efficiency of heat recovery varied from 15.1% to 54.8% when the temperature of heat source varied from 135 °C to 175 °C and saturated steam of 100 °C was produced.